Vented explosion of hydrogen/air mixture: An intercomparison benchmark exercise. (2nd April 2019) - Vyazmina, E.; Jallais, S.; Krumenacker, L.; Tripathi, A.; Mahon, A.; Commanay, J.; Kudriakov, S.; Studer, E.; Vuillez, T.; Rosset, F.
Abstract: Explosion venting is a widely used mitigation solution in the process industry to protect indoor equipment or buildings from excessive internal pressure caused by accidental explosions. However, vented explosions are very complicated to model using computational fluid dynamics (CFD). In the framework of a French working group, the main target of this investigation is to assess the predictive capabilities of five CFD codes used by five different organizations by means of comparison with recent experimental data. On this basis several recommendations for the CFD modelling of vented explosions are suggested. Highlights: CFD codes. Modeling of vented explosion (VEX). Comparison of simulations with experimental results. Recommendations for VEX modeling.